Prolactinomas: Prognostic Factors of Early Remission After Transsphenoidal Surgery - Zielinski, Grzegorz; Ozdarski, Marcin; Maksymowicz, Maria; Szamotulska, Katarzyna; Witek, Przemysław (Frontiers in Endocrinology, 2020)
Background and objective: Most patients with prolactinomas receive pharmacological treatment only, resulting in limited research on the predictors of successful prolactinoma surgery. In this study, we analyzed whether early postoperative serum prolactin concentrations and selected tumor characteristics could predict early, hormonal remission after removal of prolactinomas. Methods: We prospectively enrolled 48 consecutive patients with prolactinomas who underwent transsphenoidal resection performed by the same surgeon. Early remission, defined as a lack of hyperprolactinemia symptoms and normalization of serum prolactin concentration, was ascertained in all patients at 3 months. We evaluated the invasiveness of prolactinomas on the Knosp grading scale and measured serum prolactin concentrations on the first postoperative day. Routine immunohistochemical analysis, evaluation for plurihormonality, and assessment of the Ki-67 proliferation index (< 3% or ≥ 3% of positive nuclei) were performed in all tumor samples. Results: Of 48 patients, 38 (79%) achieved early biochemical remission at 3 months. Patients in early remission at 3 months had lower serum prolactin concentrations on the first postoperative day than patients with recurrent or persistent hyperprolactinemia (p < 0.001). Using univariate logistic regression, larger maximum tumor diameter (p=0.014), higher Knosp grade (p<0.001), and plurihormonality predicted remission at 3 months (p=0.021). However, using multivariate stepwise logistic regression, only the Knosp grade remained significant (p < 0.001). Conclusions: Radiological assessment of prolactinoma invasiveness (Knosp grades) and early postoperative serum prolactin concentrations are important predictors of early remission following transsphenoidal prolactinoma resection.